Multitargeting approaches to cognitive impairment: Synthesis of aryl-alkylpiperazines and assessment at cholinesterases, histamine H3 and dopamine D3 receptors. (15th January 2023) - Aranha, Cecília M.S.Q.; Reiner-Link, David; Leitzbach, Luisa R.; Lopes, Flavia B.; Stark, Holger; Fernandes, João Paulo S.
Graphical abstract: Abstract: Multitargeting ligands on enzymes and receptors may generate a profile for a potential treatment of cognitive impairment. Considering this, a set of 21 substituted aryl–alkyl-piperazines were designed, prepared and tested for their binding affinities at histamine H3 and dopamine D3 receptors (H3 R and D3 R, respectively) as well as acetyl- and butyrylcholinesterases (AChE/BChE) as potentially synergistic profile. Initial screening of the compounds at H3 R and D3 R was done at 1 or 10 µM and 100 µM at AChE and BChE assays. The most promising compounds were then evaluated in full concentration–response curves to estimate the K i and IC50 values. Results showed that several compounds were ligands at H3 R (n = 10), D3 R (n = 6), AChE (n = 3), and BChE (n = 9). Compounds LINS05006 ( K i H3 R 2.8 µM; D3 R 0.7 µM; IC50 BChE 26.3 µM) and LINS05015 ( K i H3 R 1.1 µM; D3 R 3.1 µM; IC50 AChE 97.8 µM; BChE 43.7 µM) are highlighted since presented affinity in three different. These results suggest that methylpiperazine moiety led to balanced activity at all three classes of targets, and longer linker provided the best affinities. These compounds presented high ligand efficiency values (LE > 0.3) and may have adequate pharmacokinetic profile as suggested by calculated physicochemical properties.